Sex and age differences in meat composition of Yeso sika deer (Cervus nippon yesoensis) reared for a short period after capture in the wild. (3rd September 2014) - Hayashida, Maki; Souma, Kousaku; Sugo, Kazuki; Araki, Shin‐ichi; Ishizaka, Fumiaki; Ueda, Masami; Kasai, Takamasa; Masuko, Takayoshi
Abstract Yeso sika deer captured in winter around Lake Akan in Hokkaido were reared for 8–10 months at Tokyo University of Agriculture in Abashiri. Six 1‐year‐old females and males and six 2‐year‐old or older (adult) females and males were slaughtered and their carcasses were processed. The chemical composition, mineral contents and fatty acid composition of the loin were measured. No marked influence of gender or age was noted in the chemical composition of loin. In the mineral contents, significant differences were noted. The potassium and sulfur contents were lower and the sodium content was higher in adult deer meat (P < 0.05, respectively) and the potassium content was higher in male deer meat (P < 0.05). Arsenic, cadmium or lead were not detected. In the unsaturated fatty acid, a significant interaction was detected (P < 0.05), and it was high in 1‐year‐old female deer meat and low in 1‐year‐old male deer meat. Significant gender or age differences were noted only in the mineral contents in the loin of deer reared for a short period after capture.